Transition to Persistent Orofacial Pain after Nerve Injury Involves Supraspinal Serotonin Mechanisms - Okubo, Masamichi (Society for Neuroscience, 2013)
The orofacial region is a major focus of chronic neuropathic pain conditions characterized by primary hyperalgesia at the site of injury and secondary hyperalgesia outside the injured zone. We have used a rat model of injury to the maxillary branch (V2) of the trigeminal nerve to produce constant and long-lasting primary hyperalgesia in the V2 territory and secondary hyperalgesia in territories innervated by the mandibular branch (V3). Our findings indicate that the induction of primary and secondary hyperalgesia depended on peripheral input from the injured nerve. In contrast, the maintenance of secondary hyperalgesia depended on central mechanisms. The centralization of the secondary hyperalgesia involved descending 5-HT drive from the rostral ventromedial medulla and the contribution of 5-HT3 receptors in the trigeminal nucleus caudalis (Vc), the homolog of the spinal dorsal horn. Electrophysiological studies further indicate that after nerve injury spontaneous responses and enhanced poststimulus discharges in Vc nociresponsive neurons were time-dependent on descending 5-HT drive and peripheral input. The induction phase of secondary hyperalgesia involved central sensitization mechanisms in Vc neurons that were dependent on peripheral input, whereas the maintenance phase of secondary hyperalgesia involved central sensitization in Vc neurons conducted by a delayed descending 5-HT drive and a persistence of peripheral inputs. Our results are the first to show that the maintenance of secondary hyperalgesia and underlying central sensitization associated with persistent pain depend on a transition to supraspinal mechanisms involving the serotonin system in rostral ventromedial medulla-dorsal horn circuits.